Brewers spent grain as a potential source of antioxidants: characterization of extracts - Lopes, Maria Teresa (2017)
NORTE-01-0145-FEDER-000004 and OCI-01-0145-FEDER-006684. Furthermore, the authors would also acknowled ge the FCT project UID/BIO/04469/2013 and would also like to thank the scientific collaboration of CBQF under the FCT project UID/Multi/50016/2013. The author T. Bonifácio - Lopes would like to acknowledge the grant UMINHO/BD/11/201